Atividades de consciência fonológica na produção do inglês como L2: uma proposta de material didático para alunos do ensino médio - Raimundo, Klécio de Assis (2023)
Observing the studies related to the process of acquiring a foreign language as an L2, one can see that there are several points of dissimilarity between the mother tongue (L1) and the L2, which end up influencing a process of phonological transfer from L1 to L2. Thus, the use of methods that appropriate concepts such as phonological awareness becomes relevant for the process of assimilation/understanding of phonetic-phonological characteristics of the target language, which correlates the students' previous phonological knowledge with the new perspectives brought by L2. To support this research, prosodic studies were used (Cagliari, 1992; Nespor, 2010; Gayer, 2015); the acoustic theory of speech production (Sousa, 1994; Barbosa; Madureira, 2015); and studies on Phonological Awareness (Freitas, 2011; Alves, 2012). In this bias, the present study seeks to propose didactic material for high school, more specifically for the English language curriculum component, which presents activities that aim at an approach focused on the use of orality linked to writing and reading, thus seeking to boost knowledge about phonological awareness that helps in the L2 acquisition process, attenuating the transfer of the phonetic-phonological characteristics of the L1 over the L2. It is hypothesized that the work that prioritizes the use of orality and the development of phonological awareness makes it possible to attenuate the phonological transfer that occurs in the process of acquiring an L2.